Near the bone - Henry, Christina, 1974- (Berkley, 2021)
"A woman trapped on a mountain attempts to survive more than one kind of monster, in a dread-inducing horror novel from the national bestselling author Christina Henry. Mattie can't remember a time before she and William lived alone on a mountain together. She must never make him upset. But when Mattie discovers the mutilated body of a fox in the woods, she realizes that they're not alone after all. There's something in the woods that wasn't there before, something that makes strange cries in the night, something with sharp teeth and claws. When three strangers appear on the mountaintop looking for the creature in the woods, Mattie knows their presence will anger William. William won't want them there, and terrible things happen when William is angry. But the creature in the woods is angry, too..."--